Proceso de atención nutricional en paciente embarazada de 20 años de edad con bajo peso y anemia. - Pincay Lorenti, Walther Howard (2022)
This clinical case is about a 20-year-old patient with a low weight pregnancy and anemia, who lives in the town of La Virgen in the city of Vinces, who was diagnosed with a low weight pregnancy, inadequate nutritional intake and anemia through a Nutritional Anamnesis, Anthropometric Evaluation and Biochemical Examinations. The medications she takes for the treatment of anemia during pregnancy are: iron + folic acid 120 mg and vitamin C. The diet of the pregnant patient is very deficient for her stage of pregnancy, due to her low economic availability and her deficiencies in recognizing foods that are rich in iron, folic acid, vitamin C, vitamin D, calcium, magnesium, etc. This leads to future complications or risks during pregnancy that affect both the child and the mother. These causes by deficit of macro and micronutrients before, during and after pregnancy leads to the mother and child to present risks such as: low weight in pregnancy and low birth weight in the child due to food deficit, the immune system is very deficient to fight any type of microorganism, virus or bacteria. The child is exposed to pathologies: Anemia, hypoglycemia, hypothermia, hypocalcemia, etc. We proceed to make an individualized nutritional plan to the patient, taking into account their socioeconomic situation and their condition of low weight and anemia, the type of diet that will be prescribed will be the diet high in carbohydrates, hyperproteic, high in unsaturated fats, high in fiber, hypo sodium, rich in iron, calcium, Potassium, phosphorus, vitamin C, vitamin D, divided into 6 meals a day, is characterized by being a diet rich in carbohydrates, proteins, unsaturated fats, rich in vitamins and minerals, low sodium and high in fiber that will help stabilize hemoglobin levels and increase your weight during pregnancy. A follow-up and monitoring plan was carried out on the patient with a 33-week pregnancy with low weight and anemia in the course of a month. Favorable results were observed in the increase of adequate weight gain and biochemical values increased to their normal range, which leads to a favorable health condition of the patient and the fetus.